كسور الناتئ الزجي المعترضة المتبدلة مقارنة بين التثبيت بأسياخ كيرشنر والبرغي الاسفنجي الضاغط, وظيفياً و شعاعياً - حلوم, غياث (Latakia University Journal -Medical Sciences Series, 2019)
The study was conducted on 24 patients, they have isolated, displaced transverse fractures of the olecranon Without accompanying injuries (Mayo classification TYPE A II) where operative intervention using compression cancellous screw 6.5 mm with Metal ring (first group 11 patients 46%),or Kirschner-wires 1.8 mm and figure of eight tension band wiring ( second group 13 patients 54%). Indirect trauma was the main cause of injury in our study 87.5%. The number of Females ranged from 8 patients 33%, Males ranged from 16 patients 67%. The median age of the patients was the sixth decade. 67% of patients aged over 50 years. The Research showed that the anatomical reduction and internal fixation with compression cancellous screw with Metal ring gave better functional and radiological results than k-wires and figure of eight tension band wiring throughout the treatment period (Up to six months of surgery) And also after three months to remove the materials . بلغ عدد المرضى في دراستنا 24 مريضاً, لديهم كسر ناتئ زجي متبدل معترض, معزول, بدون أذيات مرافقة نمط TYPE A II حسب تصنيف Mayo تم استجدالهم جراحياً ببرغي طويل اسفنجي ضاغط 6.5 مم مع حلقة معدنية ( المجموعة الأولى 11 مريض بنسبة 46%), أو باستخدام أسياخ كيرشنر 1.8 مم مع السلك المعدني الموتر على شكل 8 ( المجموعة الثانية 13 مريض بنسبة 54%). كان الرض غير المباشر يشكل السبب الرئيسى للإصابات في دراستنا 87.5 % . تراوح عدد الإناث 8 مريضة بنسبة مئوية 33 %, وتراوح عدد الذكور 16 مريض بنسبة 67 % . تراوحت أعمار المرضى الذين تم متابعتهم في دراستنا 32- 63 سنة. العمر الوسطي لفترة حدوث الكسر كان العقد السادس, أكثر المصابين أعمارهم فوق 50 سنة, والذين يشكلون67 % من إجمالي عدد المرضى. اظهرت نتائج البحث ان الرد التشريحي والتثبيت ببرغي اسفنجي ضاغط مع حلقة معدنية, أعطى نتائج وظيفية وشعاعية أفضل من استخدام أسياخ كيرشنر المتوازية مع السلك المعدني الموتر على شكل 8 طوال فترة العلاج ( حتى ستة أشهر من الجراحة), وأيضاً بعد ثلاث اشهر على نزع مواد الاستجدال .